Correlation of Puberty Status Effect of Teenage Islamic Students with Oral Hygiene and Gingiva Condition - Cahyo Nugroho; Agung Widyagdo; Culia Rahayu; Lely Tri Wahyuni (Science Midwifery, 2022)
Islamic boarding schools are social, religious institutions that become educational vehicles for Muslims who desire to investigate the religious sciences; someone accompanies a teacher wherever they go or settle in a cottage to learn science (santri/student at the muslim school). Adolescents at puberty experience growth characterized by physiological and hormonal influences on their physical appearance. Visible changes can affect their behavior, transition period, and health problems, especially in dental and oral health and gingiva. The teeth and mouth are the most crucial hygiene in the human body, becoming a significant problem in adolescent health. The absence of teeth and mouth for gingiva is frequently used as a sign of diseased periodontal tissue. This study was conducted to assess the hormonal impacts of adolescents with poor dental hygiene and gingival diseases. This type of research uses a cross-sectional design. The research sample was conducted on Daar El Fikri Islamic Boarding School adolescents, with as many as 40 people. The measuring instrument uses a questionnaire, the Oral Hygiene Index Simplified (OHI-S), and the Gingival Index. The Spearmant Correlation test carried out data analysis. The results of this student girl at the Muslim school are that the average age of puberty adolescents and experiencing a cycle turns out that oral hygiene is not good and the gingivitis has mild inflammation, this occurs due to hormonal effects.